2016
DOI: 10.12659/pjr.899710
|View full text |Cite
|
Sign up to set email alerts
|

Renal Artery Injury Secondary to Blunt Abdominal Trauma – Two Case Reports

Abstract: SummaryBackgroundBlunt abdominal trauma is routinely encountered in the Emergency Department. It is one of the main causes of morbidity and mortality amongst the population below the age of 35 years worldwide. Renal artery injury secondary to blunt abdominal trauma however, is a rare occurrence. Here, we present two such cases, encountered in the emergency department sustaining polytrauma following motor vehicle accidents.Case ReportWe hereby report two interesting cases of renal artery injury sustained in pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Our patient's renal artery injury was severe. This is in contrast to what renal artery injury patients have who generally had minor renal artery injuries and underwent conservative management [1,2,10]. In a cohort published by Sangthong et al, only 8.7% of patients underwent operative renal artery reconstruction [2].…”
Section: Discussionmentioning
confidence: 92%
“…Our patient's renal artery injury was severe. This is in contrast to what renal artery injury patients have who generally had minor renal artery injuries and underwent conservative management [1,2,10]. In a cohort published by Sangthong et al, only 8.7% of patients underwent operative renal artery reconstruction [2].…”
Section: Discussionmentioning
confidence: 92%
“…Since Von Recklinghausen initially characterized it in 1861, less than a thousand cases have been published in the literature. 4 Blunt renal injuries in pregnancy are seldom isolated, with resultant renal vascular injury following this type of injury being extremely rare. The U. S. National Trauma Databank reviewed 945,326 patients with blunt trauma.…”
Section: Discussionmentioning
confidence: 99%
“… 3 Zahoor Ahmed et al reported two young male cases of traumatic renal artery occlusions following polytrauma. 4 The first patient underwent emergency nephrectomy, while the other case underwent endovascular revascularization. Unfortunately, due to prolonged ischemia revascularization was not achieved.…”
Section: Discussionmentioning
confidence: 99%